PERAN PAKUBUWONO X DALAM PEGEMBANGAN DAKWAH ISLAM DI SURAKARTA 1893-1939 - M Mulyanto (MAMBA'UL 'ULUM, 2021)
The Role of Pakubuwana X in the Development of Islamic Da'wah in Surakarta 1893-1939 was inseparable from the socio-political dynamics that occurred, where the Dutch East Indies Government changed its policy from power expansion to ethical politics or commonly known as the politics of reciprocation. As a result, zending schools were born that carried out the Christian mission in the educational institution. Pakubuwana X as the King who has the title Sayidin Panotogomo, the position as the highest leader of the Islamic religion feels objected if his people embrace another. He was not happy with the establishment of zending-run schools in the Surakarta area that carried a Christian mission. Therefore, among the efforts to fortify its people from the spread of Christianity by establishing Mambaul Ulum. The focus of research is to determine The Role of Pakubuwana X in The Development of Islamic Da'wah in Surakarta in 1893-1939. This research is a qualitative type, namely research that intends to understand the phenomena experienced by the research subjects by examining various phenomena that occurred during the reign of Pakubuwana X. With the descriptive method, which is a method of examining the status of a group of humans, an object to provide a systematic, factual and accurate picture of the facts and phenomena being studied. From this it can be described The Role of Pakubuwana X in The Development of Islamic Da'wah in Surakarta in 1893-1939 and various related factors and indicators that support the development of this da'wah. From the results of this study it can be concluded that The Role of Pakubuwana X in The Development of Islamic Da'wah in Surakarta in 1893-1939 is very large. This can be seen from the increasing number of syi'ar Islam. Kauman is the center of Islamic activity. Various religious activities such as recitation, Islamic schools and major Islamic events continue and still exist. The rise of syi'ar Islam can also be seen from the increase in the number of people praying in congregation at Masjid Agung, for example, Friday prayers, Dhuhur and Ashr, the number of congregations is getting more and more crowded. Khutbah Jum’at were translated into Javanese and Arabic, previously Khutbah Jum’at used Arabic, installed loudspeakers and broadcast directly by SRI radio (Broadcast Radio Indonesia) belonging to Kasunanan Surakarta.